An open-label study of aripiprazole for methamphetamine induced psychosis - Sulaiman, A.H.; Gill, J.S.; Said, M.A.; Habil, M.H.; Zainal, N.Z.; Guan, N.C. (2012)
Objective: This study aimed to explore the therapeutic effects and tolerability of aripiprazole in the treatment of psychosis among methamphetamine dependent patients. Methods: This was an open label single arm prospective study conducted at the University Malaya Medical Centre (UMMC). The study subjects included treatment naive patients with a current diagnosis of methamphetamine dependence with co-occurring acute psychotic symptoms based on the Diagnostic and Statistical Manual of Mental Disorders-IV (DSMIV). Eligible patients were treated with an initial dose of 5-10 mg aripiprazole followed by flexible doses (5-15mg/day) from day 2 to 14. Results: Out of 49 patients enrolled, 41 patients (83.7) completed the study. At baseline the mean PANSS total score was 79.2 +/- 13.7 and the mean CGI-S score was 4.3 +/- 0.5. There was a statistically significant decline in the mean PANSS-total and CGI-S scores over the course of the study. The mean reduction was 27.6 +/- 21.4 point (p < 0.05, 95 Cl (-34.8, -20.4)) from baseline on day 14 for total PANSS score and 2.0 +/- 1.2 point (p < 0.05, 95 Cl (-2.4, -1.6) for CGI-S. Aripiprazole was generally well tolerated during the study. Adverse events were reported in 10 (20.4) patients. No statistically significant changes were noted with respect to movement-related adverse events. Conclusions: This study found that aripiprazole improved the psychotic symptoms associated with methamphetamine use. It was generally well tolerated with mild to moderate adverse events. Based on these results aripiprazole might be an effective and safe option for the treatment of methamphetamine induced psychosis.